1996
DOI: 10.1002/(sici)1098-1101(1996)11:2<61::aid-jca2>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid apheresis in an animal model causes in vivo changes in lipoprotein electrophoretic patterns

Abstract: Lipid apheresis, a new extracorporeal procedure based on plasma delipidation and showing promise as a possible treatment for atherosclerosis, was recently reported for the first time from this laboratory [Cham et al., J Clin Apheresis 10:61–69. 1995]. In the present study lipid apheresis was applied to hypercholesterolemic and normocholesterolemic roosters to examine its effect on plasma lipoprotein particles. This procedure resulted in conspicuous changes in electrophoretic patterns of plasma lipoproteins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…LA may also increase reverse cholesterol transport by removing cholesterol from the body by way of extracting cholesterol directly from plasma which is the essence of the LA procedure [6,7,12,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LA may also increase reverse cholesterol transport by removing cholesterol from the body by way of extracting cholesterol directly from plasma which is the essence of the LA procedure [6,7,12,21].…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been shown that LA may modulate reverse cholesterol transport by increasing cholesterol efflux. This is achieved because LA results in the formation of apolipoprotein A-1 [12,21], discoidal HDL [22] and pre-beta HDL particles [7]. These HDL particles are regarded as good cholesterol acceptors from cellular cholesterol and may be important components of reverse cholesterol transport [19,20,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At approximately 150 minutes after LA, the changes in the HDL pattern had almost returned to the original pre-LA treatment patterns. Concomitant to the changes in the HDL pattern was the immediate reduction in plasma cholesterol concentrations, which was sustained also for 150 minutes [17]. Saturated LCAT kinetics was observed for 150 minutes after reinfusion of delipidated plasma in the hypercholesterolemic animals but not normocholesterolemic animals, suggesting that a larger pool of FC was being mobilized in the hypercholesterolemic animals [18].…”
Section: Batch Type Lipid Apheresismentioning
confidence: 99%